A phase 1 trial of SGN-CD70A in patients with CD70-positive diffuse large B cell lymphoma and mantle cell lymphoma - Phillips, Tycel (Invest New Drugs, 2018)
Purpose This first-in-human study evaluated SGN-CD70A, an antibody-drug conjugate (ADC) directed against the integral plasma membrane protein CD70 and linked to a pyrrolobenzodiazepine (PBD) dimer, in patients with relapsed or refractory (R/R) CD70-positive non-Hodgkin lymphoma (NHL) including diffuse large B cell lymphoma (DLBCL), mantle cell lymphoma (MCL), and Grade 3b follicular lymphoma (FL3b). Methods SGN-CD70A was administered intravenously on Day 1 of 3-week cycles beginning at 8 mcg/kg with planned dose escalation to 200 mcg/kg. Due to observations of prolonged thrombocytopenia, the study was amended to dose every 6 weeks (q6wk). Results Twenty patients were enrolled and treated with SGN-CD70A. The maximum tolerated dose of SGN-CD70A was 30 mcg/kg q6wk. The most common adverse events (AEs) reported were thrombocytopenia (75%), nausea (55%), anemia (50%), and fatigue (50%). The onset for treatment-related thrombocytopenia typically occurred during Cycle 1. Most of the treatment-related events of thrombocytopenia were ≥ Grade 3. Antitumor activity in patients included 1 complete remission (CR) and 3 partial remissions (PRs), 2 of which were ongoing for at least 42.9 weeks. SGN-CD70A exposures were approximately dose proportional, with a mean terminal half-life of 3 to 5 days. Conclusions While modest single-agent activity was observed in heavily pretreated NHL patients, the applicability of SGN-CD70A is limited by the frequency and severity of thrombocytopenia, despite the long-term response with limited drug exposure. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10637-018-0655-0) contains supplementary material, which is available to authorized users.